2009
DOI: 10.1111/j.1365-2559.2009.03273.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive cellular response in the lamina propria of the colorectal adenoma–carcinoma sequence

Abstract: Progressive cellular responses in the lamina propria could be involved in the adenoma-carcinoma transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 45 publications
4
25
0
Order By: Relevance
“…These cells in the tumor stroma may function as a double-edged sword because they play an important role in both the anticancer response [39,40] and in favoring cancer progression in some certain conditions [26,41,42]. By both the quantitative and qualitative techniques, IDO has been found to be expressed by many types of cells in the tumor microenvironment including tumor cells, fibroblasts, endothelial cells (microvessels), dendritic cells, and macrophages in various cancers [12,20,43,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells in the tumor stroma may function as a double-edged sword because they play an important role in both the anticancer response [39,40] and in favoring cancer progression in some certain conditions [26,41,42]. By both the quantitative and qualitative techniques, IDO has been found to be expressed by many types of cells in the tumor microenvironment including tumor cells, fibroblasts, endothelial cells (microvessels), dendritic cells, and macrophages in various cancers [12,20,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…DIHC further confirmed that those IDO-positive surrounding noncancerous cells (brown in g, h, i) were myofibroblasts (red color, labeled by SMA-alpha in g), macrophages (red color, labeled by CD68 in h), and dendritic cells (red color, labeled by S100 in i , and IDO/S100 (to label dendritic cells; monoclonal anti-SMA-alpha, anti-CD68, and anti-S100 antibodies were all purchased from Dako, Carpinteria, CA, USA) according to the manufacturer's instructions and the method described in our publications [25,26]. In brief, the slides were incubated for 30 min with anti-IDO antibody after antigen retrieval and then incubated with labeled polymer-horseradish peroxidase-antimouse and antirabbit antibodies for 10 min at room temperature.…”
Section: Tissue Specimens From Esccs and Controlsmentioning
confidence: 99%
“…IHCs for IL-6 and NF- κ B were performed with Vectastain Elite ABC Kit (Vector Laboratories Inc., Burlingame, CA, USA) according to the manufacturer's instructions and our published method [24]. The following primary antibodies were used: rabbit anti-IL-6 polyclonal antibody (working dilution 1 : 100, Santa Cruz Biotechnology Inc., Santa Cruz, CA, USA) and rabbit anti-NF- κ B polyclonal antibody (working dilution 1 : 100, Santa Cruz Biotechnology Inc., Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, we have demonstrated that the SMA-α-positive myofibroblast was with a high proliferation capacity in the ESCC tumor stroma and together with the increased infiltration of lymphocyte and macrophage in the same field. A growing body of evidence suggests that fibroblast/myofibroblast activation is a critical factor in promoting cancer invasion and growth [27,31]. In addition, myofibroblast in the tumor stroma is also one of the main cellular sources for COX-2 [29], whereas COX-2 has been demonstrated to be a potential growth factor for cancer cells and a strong stimulator for angiogenesis [13].…”
Section: Discussionmentioning
confidence: 99%
“…To examine the proliferative capacity of different types of tumor stromal cells, double IHCs with proliferating cell nuclear antigen (PCNA)/CD3, PCNA/CD68, and PCNA/ SMA-alpha antibodies (rabbit anti-PCNA antibody was purchased from Santa Cruz Inc, Santa Cruz, CA, USA) were done with EnVision Doublestain System kit (DAKO, Carpinteria, CA, USA) according to the manufacturer's instructions and our published method [27]. The enzyme substrate 3, 3′-diaminobenzidine tetrachloride (DAB) was used for the visualization of anti-PCNA immunoreactivity and Fast Red for the visualization of anti-CD3, anti-CD68, and anti-SMA-alpha immunoreactivities.…”
Section: Double Immunohistochemical Identification Of Proliferation Amentioning
confidence: 99%